Memahami dan Menggali Potensi Diri untuk Menggapai Kesuksesan - Wildan Halid (Institut Agama Islam (IAI) Nurul Hakim, 2022)
Knowledge is power. Everyone has the opportunity to have knowledge. However, even if someone has knowledge if there is no effort to optimize their potential, it will not mean anything. Potential is an amazing thing that is owned by every human being. Knowledge will not appear suddenly, for it requires a long process based on one's grasping power. To understand our potential, we need understanding, strategies, and techniques on how to generate potential in ourselves, generating potential in ourselves is an innate ability from birth. This potential becomes a hidden natural ability that can be maximized. This ability can be optimized through individual efforts to learn and maximize the potential within. This research is a library research with a comprehensive study of paradigms and concepts that describe how to maximize one's potential to achieve success.